(untitled) (Research, Society and Development, 2022)
Titanium is a complex element and presents more than one crystallographic form, at room temperature it has a hexagonal crystal structure that transforms into a body-centered structure at 800ºC, and a melting point of 1670ºC ± 5ºC. Titanium alloys have superior mechanical properties to Ti c.p. in addition to excellent biocompatibility, a characteristic makes them the material of choice in orthopedic and dental applications. The alloy used in this study was the Ti-6Al-4V ELI alloy, obtained in cylindrical shape, sanded, and subsequently subjected to thermochemical treatment with NaOH. The physicochemical characterization was performed by the techniques of X-ray fluorescenic spectrometry (XRF), scanning electron microscopy (SEM), X-ray diffractometry (XRD) and X-ray excited photoelectron spectroscopy (XPS). A biphasic structure (α and β) and the formation of an alkali titanate hydrogel (sodium titanate (Na2Ti5O11)) on the surface were observed, due to the reaction of the TiO2 film with the NaOH solution. It is concluded the immersion of the samples in NaOH, resulting in the crystallization of the titanate hydrogel layer, may favor the formation of calcium phosphates, as well as the bone/implant interaction.